Artificial Intelligence in Primary Education: A Philosophy of Science Inquiry into the Ontological, Epistemological, and Axiological Roles of Elementary School Teachers - Yanti Restiawati; Amir Masruhim (Borneo Educational Journal (Borju), 2026)
The rapid expansion of Artificial Intelligence (AI) in education has largely been framed through instrumental benefits such as efficiency and personalization, yet its deeper implications for primary education, where teaching is inherently relational, moral, and developmentally sensitive, remain underexplored. This study examines how AI reshapes the meaning of teaching, knowledge, and educational values for elementary school teachers through a philosophy of science lens. Using a thematic narrative review, literature from Scopus, Web of Science, and Google Scholar was screened, yielding 34 core sources that were analyzed through ontological, epistemological, and axiological dimensions. The findings indicate that AI operates as a set of socio-technical systems, including generative tools, adaptive platforms, and analytic dashboards, that mediate instructional decisions and subtly redistribute agency between teachers and technologies. Epistemologically, AI reshapes knowledge authority by privileging algorithmic outputs, although teacher-led AI literacy and critical mediation can strengthen rather than weaken teachers’ epistemic roles. Axiologically, AI introduces ethical tensions related to teacher wellbeing, children’s vulnerability, data privacy, and equity, particularly within the Indonesian primary education context characterized by uneven infrastructure and digital literacy. The study concludes that AI is not value-neutral in primary schooling; it actively participates in redefining who acts, who knows, and what is valued in the classroom. AI can contribute positively to learning only when positioned as a supportive resource under strong human oversight that preserves teachers’ moral, relational, and epistemic functions, thereby safeguarding the human core of primary education in an increasingly algorithmic world.